1998
DOI: 10.1111/j.1398-9995.1998.tb03869.x
|View full text |Cite
|
Sign up to set email alerts
|

Sense of smell in allergic and nonallergic rhinitis

Abstract: Hyposmia is a fairly common complaint in patients with long-continuing allergic or nonallergic rhinitis. Other factors such as aging, smoking, or nasal surgery may affect olfaction, but these have been little studied in rhinitis-related hyposmia. The purpose of this study was to measure and compare olfactory thresholds in 105 rhinitis patients and 104 healthy controls and to analyze possible relationships between the sense of smell and rhinitis, age, sex, smoking, prick-test results, nasal resistance, and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 8 publications
(1 reference statement)
4
39
2
1
Order By: Relevance
“…If this is the case, the effect is likely due to inflammation within the olfactory epithelium, as has been documented by Kern (2000), rather than by blockage of airflow to the olfactory epithelium. Numerous studies have noted a direct correlation between histopathological changes in the olfactory mucosa and measures of olfactory function in patients with chronic rhinosinusitis (Downey et al 1996;Moll et al 1998;Apter et al 1992;Simola and Malmberg 1998;Doty and Mishra 2001). Strong relationships are not found between airway patency and olfactory dysfunction except in cases of severe blockage, as from extreme polyposis (Doty and Mishra 2001).…”
Section: Discussionmentioning
confidence: 96%
“…If this is the case, the effect is likely due to inflammation within the olfactory epithelium, as has been documented by Kern (2000), rather than by blockage of airflow to the olfactory epithelium. Numerous studies have noted a direct correlation between histopathological changes in the olfactory mucosa and measures of olfactory function in patients with chronic rhinosinusitis (Downey et al 1996;Moll et al 1998;Apter et al 1992;Simola and Malmberg 1998;Doty and Mishra 2001). Strong relationships are not found between airway patency and olfactory dysfunction except in cases of severe blockage, as from extreme polyposis (Doty and Mishra 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Chronic rhinitis may impair the smell [16]. In patients with inferior turbinate hypertrophy the olfactory alteration seems to be caused by blockage of airflow to the olfactory receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have previously reported smell disorders in patients with SAR [3,4,5,6,7,8,9] and PAR [8,9] linked to inflammation and not to nasal obstruction. Using ARIA criteria, we demonstrated in a previous study that PER induces a moderate loss of smell [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported smell disorders associated with SAR [3,4,5,6,7,8,9], few studies have addressed the potential loss of smell in patients with PAR [8,9]. It is well known that the association between AR and chronic rhinosinusitis seriously harms the sense of smell [10,11].…”
Section: Introductionmentioning
confidence: 99%